Att förhandla litterärt värde: Sami Said och Väldigt sällan fin - Forslid, Torbjörn; Helgason, Jon; Larsson, Lisbeth; Lenemark, Christian; Ohlsson, Anders; Steiner, Ann (Tidskrift för litteraturvetenskap, 2013)
Negotiating Literary Value. The Case of Sami Said. This article aims to highlight how literary value is constructed today: how it is created and negotiated. It seeks to develop a perspective that considers the manifold and complex value-negotiation process. In accordance with Barbara Herrnstein Smith, the article argues that literary value is generated by a constant and continuous series of negotiations between production and sale: the institutions, groups of readers, and individuals who are part of the value-making process. A number of different values circulate among different stakeholders – trade, educational, aesthetic, personal, and so on – and the negotiations take place in accordance with the dictates of the respective needs, interests, and resources of these stakeholders. While Barbara Herrnstein Smith’s theories on literary value remain influential, they have rarely been tested empirically. The basic premise of the article is that the process of value creation has to be discussed from new perspectives based on empirical research. The article presents a case study of the Swedish author Sami Said’s literary debut – the critically acclaimed Väldigt sällan fin – and the negotiation process before and after its publication. The fact that Said was unknown at the time of his debut most likely foregrounded the visible negotiation of literary value in his case, but we believe that the process can be seen as an example of a continual and on-going practise in the literary sphere as a whole. The analysis shows that different agents claimed values and positions both in relation to the book and to each other. For example, marketing and publishing paratexts emphasised values of knowledge, institutionalised literary criticism valued the aesthetic qualities of the novel, while readers writing on the Internet took a more emotional and subjective position. The valuation also went back-and-forth between reading the novel as expressing a particular, non-Swedish experience with biographical overtones, and understanding it as manifesting universal existential values.